2022
DOI: 10.1002/ecy.3662
|View full text |Cite
|
Sign up to set email alerts
|

A hurricane alters the relationship between mangrove cover and marine subsidies

Abstract: As global change alters the composition and productivity of ecosystems, the importance of subsidies from one habitat to another may change. We experimentally manipulated black mangrove (Avicennia germinans) cover in 10 large plots and over a 5-year period (2014-2019) quantifying the effects of mangrove cover on subsidies of floating organic material (wrack) into coastal wetlands. As mangrove cover increased from 0% to 100%, wrack cover and thickness decreased by ~60%, the distance that wrack penetrated into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…The high-water levels, storm surge, and strong winds from Hurricane Isaias caused wrack mats to enter into regions of the study area where wrack was not found before the storm passed, nor after for the rest of the study. As Peng et al (2022) [40] observed from Hurricane Harvey, a strong storm can move wrack deeper into a wetland than otherwise found during other normal conditions. The largest clusters of wrack were found on the western edge of the study area, close to largest nearby water body-the Harbor River.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The high-water levels, storm surge, and strong winds from Hurricane Isaias caused wrack mats to enter into regions of the study area where wrack was not found before the storm passed, nor after for the rest of the study. As Peng et al (2022) [40] observed from Hurricane Harvey, a strong storm can move wrack deeper into a wetland than otherwise found during other normal conditions. The largest clusters of wrack were found on the western edge of the study area, close to largest nearby water body-the Harbor River.…”
Section: Discussionmentioning
confidence: 82%
“…In each of those respective studies, they established the opportunity for wrack to benefit the overall system, despite the time required for these to be had. Even simple identification of wrack falling beneath the canopy in our study suggests a positive impact because the matted down wrack can now serve as a home to several species of aquatic creatures [40,45]. It has even been suggested by one researcher that the warm climate found on the South Carolina coast can enhance the decomposition of wrack detritus to benefit the entire salt marsh [25].…”
Section: Discussionmentioning
confidence: 84%